PREDICTORS OF THE INCIDENCE OF PREECLAMPSIA IN PREGNANT WOMEN - Yasinta Anugrah Heni; Noor Hidayah; Muhamad Jauhar (Universitas Muhammadiyah Kudus, 2026)
Background: Preeclampsia is one of the leading causes of maternal morbidity and mortality in Indonesia, characterized by increased blood pressure and proteinuria after 20 weeks of gestation. Risk factors that often play a role in the incidence of preeclampsia include pre-pregnancy weight (obesity), family history of hypertension, and twin pregnancies.Objective: This study aims to determine the relationship between pre-pregnancy weight, family history of hypertension, and twin pregnancies with the incidence of preeclampsia at Sunan Kudus Hospital.Methods: This study used a quantitative design with a cross-sectional retrospective case control approach. Independent variables are pre-pregnancy BB, family history of hypertension and twin pregnancies while dependent on the incidence of preeclampsia. This research was conducted at RSI Sunan Kudus in August 2025. The sample of 252 pregnant women in 2024 through total sampling, consisting of 63 mothers with preeclampsia (cases) and 189 mothers without preeclampsia (control). Data were obtained from medical records and analyzed using the Chi-Square test.Results: showed a significant association between prepregnancy weight and the incidence of preeclampsia (p = 0.001; OR = 49.6; CI 95%: 14.29–172.12) and a significant association between family history of hypertension and the incidence of preeclampsia (p = 0.001; OR = 16.75; 95% CI: 9.67–28.99). However, there was no significant association between twin pregnancies and preeclampsia (p = 0.718; OR = 0.58; 95% CI: 0.16–2.07).Conclusions: There was a significant association between pre-pregnancy weight and family history of hypertension and the incidence of preeclampsia, however twin pregnancies were not significantly associated. It is recommended that health workers increase early detection and education for pregnant women with high risk factors to reduce the incidence of preeclampsia.